Effective Use of Padlet as a Tool to Enhance Students’ Engagement with the Concept Learning: A Case Study - Agavekar, Rujuta; Bhore, Poonam; Moharir, Mrunal (Journal of Engineering Education Transformations, 2026)
Active learning is a key feature of outcome-based education which can be implemented by using various tools made available by technology such as Padlet, Wakelet etc. Padlet is a web 2.0 tool which can be used effectively to share information, audio and video files on virtual walls. The paper discusses the effectiveness of Padlet as an ICT tool to enhance students’ engagement with concept learning in the post pandemic era. A Padlet wall was used by the course instructor and the students of the third-year undergraduate Mechanical Engineering program, to generate a digital repository of concept-based questions and answers for the course Applied Thermodynamics. This activity triggered peer discussion outside the classroom in a stress-free environment and encouraged students to contribute to the Padlet wall in a competitive spirit. Active participation of the students in the teaching learning process with the use of Padlet promotes collaborative learning and ensures thorough understanding of the key concepts which has direct impact on the attainment of Course Outcomes. Hence, in the present study students’ performance in the Continuous Internal Evaluation (CIE) and Semester End Evaluation (SEE) is discussed in terms of the attainment levels of the Course Outcomes. It was observed that most of the course outcomes are attained with highest level which was remarkable as students were just venturing back into offline mode after COVID 19 pandemic. The study shows that students have a strong and unanimous positive perception of the use of the Padlet as proved by Wilcoxon test.